Extension of the known range of the snapping shrimp Alpheus christofferseni Anker, Hurt and Knowlton, 2007 (Caridea: Alpheidae) - Gabriel Lucas Bochini; Rodrigo Guéron; Mariana Terossi; Alexandre Oliveira Almeida (Nauplius, 2023)
Abstract Alpheus christofferseni Anker, Hurt and Knowlton, 2007 was described based on four specimens from Atol das Rocas, northeastern Brazil, and one specimen from Bocas del Toro, the Caribbean coast of Panama. Here, we report the collection of two specimens from Pernambuco, Brazil (~ 8°41’S), thus increasing the knowledge on species distribution along the Brazilian coast by approximately five latitudinal degrees south of its type locality (Atol das Rocas, Rio Grande do Norte, ~ 3°51'S). We also report a substantial increase in the known bathymetric distribution from shallow intertidal to approximately 51 m. Notes on morphological variation are provided based on the new material, and the first sequence of the 16S ribosomal subunit gene for the Brazilian coast is provided and compared with congeners.